Impactos Territoriais da Criação de Assentamentos Rurais: o caso dos PA s Timbó e Mata Verde Espírito Santo/RN - Lima, Silvânia Félix de (2015)
This study analyzes, from redemption of the land struggle, the territorial impacts due the stablishment of two rural settlements (Timbó and Mata Verde) here understood as "Territories of Hope in Espírito Santo, a norteriograndense town, located in the state of Rio Grande do Norte, in Brazil northeast. It is housed in the South Coast microregion, Potiguar East Mesoregion which means an area of 158 sq. km, equivalent to 0.29% of the state surface (IBGE, 2000). To do so, some methodological procedures were used, such as: literature review, secondary survey data and field research. Initially, a brief reflection on the peasantry and territories was performed, needful categories for understanding the permanence of the peasantry in a society modeled after the capitalist mode of production and the understanding of territorial changes resulting from the creation and implementation of agrarian reform settlements.Then, it was done a study of the recent process of spatial and territorial struggle for land in Rio Grande do Norte emphasizing the spatial distribution of land conflicts and territorial fighting by land through the creation of rural settlements. Subsequently, it was performed a sort of characterization of Espírito Santo focusing the recent organization of its agrarian space in order to identify the factors that provoked the creation of settlements located there, recovering the history of struggle that culminated in the creation of settlements, conducting a brief description of the territorial configuration of them. Finally, we present a description of the territorial impacts of the creation of Timbó and Mata Verde settlements.